Did the resurgence of childhood lower respiratory infections offset the initial benefit of COVID-19-related non-pharmaceutical interventions in children? A time-series analysis - Inès Fafi; Zein Assad; Léa Lenglart; Zaba Valtuille; Florentia Kaguelidou; Camille Aupiais; Aurélie Bourmaud; Alexis Rybak; Stéphane Bechet; Corinne Levy; Robert Cohen; Bruno Frandji; et al. (BMC Medicine)
Abstract Background Following non-pharmaceutical interventions (NPI) lifting in 2021, an important surge in childhood lower respiratory tract infections (LRTI) was reported in several countries, raising major concerns about the middle-term consequences of such interventions. Whether this recent upsurge overwhelms the initial benefit of NPI remains unknown. Methods We conducted an interrupted time-series analysis based on exhaustive national surveillance systems. All hospitalisations from January 2015 to March 2023 and all ambulatory visits for LRTI from a network of 110 paediatricians from June 2017 to March 2023 were included. The main outcome was the monthly incidence of children hospitalised for LRTI per 100,000 over time, assessed by a seasonally adjusted quasi-Poisson regression model. Results We included 845,047 hospitalisations. The incidence of hospitalisation for LRTI significantly decreased during the NPI period (− 61.7%, 95% CI − 98.4 to − 24.9) and rebounded following NPI lifting, exceeding the pre-NPI baseline trend (+ 12.8%, 95% CI 6.7 to 19.0). We observed similar trends for hospitalisation due to bronchiolitis, pneumonia and pneumonia with pleural effusion, along with ambulatory LRTI. Overall, despite the recent rebound, 31,777 (95% CI, 25,375 to 38,179) hospitalisations for paediatric LRTI were averted since NPI implementation up to 2023. Conclusions Three years after their implementation, despite an increase in LRTI incidence, the middle-term impact of NPI remains highly beneficial in preventing overall paediatric LRTI. The implementation of some societally acceptable NPI, particularly during epidemics, may be considered in the future to further reduce the burden of paediatric LRTI.